A data communication network for administrative purposes within the EU - Kari T. Sipilä (Bank of Finland, 1996)
The study assesses data communication requirements within the EU as it concerns Member State officials, EU bodies and the Community.A survey of current projects and their backgrounds is given.In addition the division of responsibilities among various bodies of the Commission are discussed. Given the EU's need for some sort of integration of data transfer services is self evident, the study investigates what possible challenges lie ahead as EU integration processes continue and its already large communications requirements continue to grow.For example, while the Commission as well as its empowered bodies have recognized the need for a unified communications architecture, the political will to implement such as system has been lacking.The report recommends the creation of a unified, universal communications architecture, that not only can handle all current types of data transfer, but anticipates growth as well.
URN:NBN:fi:bof-20140807212
Keywords: 330; The European Union; A Data communication; The Authorities